Asymptotics for general nonstationary fractionally integrated processes without prehistoric influence. Issue 4 (2002) - Wang, Qiying; Lin, Yan-Xia; Gulati, Chandra
Abstract : This paper derives a functional limit theorem for general nonstationary fractionally integrated processes having no influence from prehistory. Asymptotic distributions of sample autocovariances and sample autocorrelations based on these processes are also investigated. The problem arises naturally in discussing fractionally integrated processes when the processes starts at a given initial date.